(3GdMdd aj TQM CHjGJ GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s
(3ChdgG (B:s
(3hgPG Mjf CHOC HTQM Tcd EYQGH CHjGJ gPG GdcJGH heYGfjg s
(3BNQgG (B:s
(3ef TQM (B( (3hEf TFJe JYGhPfG YhGPG(B" (3hCfTOg GHf LfHi HGdPGd ZjQ eYLeI hgh GdUhGH Ef TGA Gddg ced LejY GdcJGH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(3986) s
Keywords: (3GdCOHs